POTENSI GETAH BUAH PEPAYA (Carica papaya L) TERHADAP MORTALITAS LARVA NYAMUK Aedes albopictus - Sri Wulandari; Arnentis '; Sri Rahayu (Biogenesis, 2012)
A research was conducted to find out the effect of papaya latex (Carica papaya L) toward the mortality of Aedes albopictus larva, in Laboratory of Biology Faculty of Education Teacher Training and Education University of Riau in November 2011 to April 2012. The method used in this research was experimental method to the preparation of a random sample consisting of 5 treatments which are repeated for 3 times. The number of larva are 10. Parameter observed is Aedes albopictus larva mortality as long as 96 hours, LC50 value and toxic response of Aedes albopictus larva which could be showed by body movement, posture and body color of larva. The data of this research was analyzed by probit and deskriptif analysis. The supporting parameters is temperature and pH of the medium. The results of the research showed that the papaya latex (Carica papaya L) could make the mortality of Aedes albopictus larva. Mortality of Aedes albopictus larva in concentration 27 ppm was 100% in 24 hours, in concentration 18 ppm was 100% in 72 hours, mortality of Aedes albopictus larva in concentration 12 ppm and 8 ppm was 80% and 50% in 96 hours. LC50 value in 24 hours was 26.30 ppm, in 48 hours was 20.41 ppm, in 72 hours was 14.12 ppm and 96 hours was 9.12 ppm. The roxic response of Aedes albopictus larva showed the mobility of the less agile, larva body roll, the larva's body parallel to the surface of the water and the color of pale white body. From the result of the research can be concluded that the papaya latex can potentially lead to death of Aedes albopictus larva and the concentration recommended for application to the environment is 9.12 ppm in 96 hours.Keywords: Aedes albopictus larva, Papaya late.